Reliability of Vertical Jump Performance evaluated with contact mat in elderly women. (10th January 2013) - Farias, Darlan L.; Teixeira, Tatiane G.; Madrid, Bibiano; Pinho, Danilo; Boullosa, Daniel A.; Prestes, Jonato
Summary The aim of this study was to evaluate the reliability of the vertical jump (VJ) using a contact mat in elderly women. Thirty‐one physically active women aged 69·5 ± 5·6 years participated in this study. Jump performance was evaluated with a contact mat. The first testing session (s1) consisted of four countermovement jumps interspersed with 40 s rest intervals. After a period of 5–7 days, volunteers performed the second session (s2) utilizing the same procedures. The intersession statistical analysis was calculated considering the two highest jumps, one obtained in each section. The intra‐session analysis utilized all eight jumps, all four from each section, and the differences between means were calculated by repeated measures ANOVA. Reliability was tested using the intra‐class correlation coefficient (ICC) and agreement by the Bland–Altman method. The intra‐ and inter‐subject variation percentage was calculated by the coefficient of variation (CV). Results: The intersession results displayed a high ICC (0·91; P<0·001) and a good agreement verified by the Bland–Altman method. There was a significant difference in the intra‐session analysis only in s2 between the jumps 2 and 4. Both in s1 and s2, the ICC was high (0·96; P<0·001; 0·95; P<0·001), and the within session reliability CV was low (10·14% and 9·07%). Conclusion: In physically active elderly women, VJ evaluation using a contact mat is a reliable method and could be used to estimate jump height. Additionally, the results of this study could serve as reference values in similar samples evaluated with the same procedures.